Optical excitation of surface plasmon polariton and waveguide modes resonances on prismatic structures - Fitio, Volodymyr; Yaremchuk, Iryna; Bobitski, Yaroslav (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The prismatic structures for excitation surface plasmon polariton and waveguide modes resonances were investigated. The first structure consists of a glass prism and thin metallic layer deposited on the prism. The second one includes an additional dielectric layer. Plasmon polariton resonance can be observed only for TM polarization at finely tuned structure parameters. Waveguide modes resonance is possible for both polarizations in the presence of the dielectric layer. We show that the first structure has the highest sensitivity of angle minimum reflectivity, whereas the second one has the highest reflectivity sensitivity to the probed liquid refractive index changes.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 929-939
Keywords: optyka; surface plasmon polaritons; waveguide mode; resonance; sensitivity